Ethnomathematics Digital Student Worksheet Using the Problem Based Learning Model to Improve Creative Mathematical Thinking for Elementary School Students - Nur Atikasari; Agus Efendi; Sri Yamtinah (Jurnal Pendidikan dan Pengajaran, 2024)
Low creative mathematical thinking ability is caused by the difficulty of learning mathematics on the division of decimal numbers. Therefore, this research aims to develop digital ethnomathematics worksheets using the PBL model to build students' creative mathematical thinking skills on division of decimal numbers in class V elementary school. This type of research is development research with the ADDIE development model. The subjects of this research were 7 material experts and 2 learning media experts. The test subjects in this research and development were 8 students. Data collection techniques include observation, interviews, and questionnaires. The data collection instrument is a questionnaire sheet. The techniques used to analyze the data are qualitative and quantitative descriptive analysis. The research results, namely the assessment results given by learning material experts, were 84.29% so they were declared very good. The assessment results by learning media experts were 90.00% so they were declared very good. The assessment results by students obtained an overall average score of 81.52%, so it was very good. It was concluded that digital ethnomathematics worksheets using the PBL model were suitable for learning. This research implies that using digital ethnomathematics worksheets using models can improve students' creative thinking.